On the Relationship between a Student Association's Endeavors to Foster a Social-Academic Climate on Campus, Students' Self-Efficacy, and Academic Motivation - Nitza Davidovitch; Ruth Dorot (MDPI AG, 2023)
The current study is a case study examining a student association's endeavors to foster a social-academic climate on campus, grant students a sense of self-efficacy, and even contribute to students' motivation. The research literature lacks empirical knowledge on the activity of student associations and their contribution to institutions of higher education and their students. Moreover, academic institutions see student associations at times as a burden, a type of labor union to be placated by the faculty and the academic institution. The research sample consisted of 122 students from a university in Israel (38 men and 84 women; mean age 25). Several questionnaires were administered to the respondents: a questionnaire on the social-academic climate on the academic campus, a questionnaire on students' academic motivation, a questionnaire on students' self-efficacy, and a sociodemographic questionnaire. From the research findings, it is evident that the activities of the student associations on the academic campus play a meaningful role in fostering students' academic motivation and self-efficacy. The research findings indicate that the scope of student association activities is positively related to the students' academic motivation and self-efficacy. Moreover, students living in student dorms were found to evaluate the activities of the student association as higher than did students who were not living in student dorms. These findings constitute a preliminary foundation for future studies on the importance of student associations in academic institutions and their contribution to the students. Furthermore, these findings highlight the need to boost and increase student associations' activities to provide students with adapted and efficient solutions to their challenges. The student association can be transformed from a burden to an asset for the academic institution.